2021
DOI: 10.1021/acs.inorgchem.1c00116
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying a Competitive Crystallization Mechanism of Upconversion Luminescent Oxyfluoride Glass Ceramics by Solid-State NMR Spectroscopy

Abstract: glass system by adjusting their compositions. The structural evolution at the atomic level driven by heat treatment and glass compositions was studied using the state-of-the-art magic-angle spinning nuclear magnetic resonance technique. From a comprehensive local structural study, we found that LaF 3 and NaLaF 4 crystals compete in crystallization in these glasses. The crystallization ability of NaLaF 4 increases with the increase of the content of Na + ions within the F-enriched phase, but for LaF 3 crystals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…This is because only at such a high BaF 2 content, the local concentration of F – ions around La 3+ and Ba 3+ is high enough to precipitate the Ba 2 LaF 7 crystal. The quantity of the F – ions attracted by the cations depends on the ability of the cations to attract F – . To estimate or characterize the abilities of the cations to attract F – , a parameter, R F–M , was defined, as follows: where M F denotes the total F content, f means the fraction (%) of the F–M species (M = La 3+ and Ba 2+ ) that were obtained via the deconvolution of the 19 F MAS spectra (Table S6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because only at such a high BaF 2 content, the local concentration of F – ions around La 3+ and Ba 3+ is high enough to precipitate the Ba 2 LaF 7 crystal. The quantity of the F – ions attracted by the cations depends on the ability of the cations to attract F – . To estimate or characterize the abilities of the cations to attract F – , a parameter, R F–M , was defined, as follows: where M F denotes the total F content, f means the fraction (%) of the F–M species (M = La 3+ and Ba 2+ ) that were obtained via the deconvolution of the 19 F MAS spectra (Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…The quantity of the F – ions attracted by the cations depends on the ability of the cations to attract F – . To estimate or characterize the abilities of the cations to attract F – , a parameter, R F–M , was defined, as follows: where M F denotes the total F content, f means the fraction (%) of the F–M species (M = La 3+ and Ba 2+ ) that were obtained via the deconvolution of the 19 F MAS spectra (Table S6). q denotes the electric charge of M , and [ M ] represents the molar ratios of La 3+ and Ba 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, these results indicated that the P 6 3 / m space group should be qualified to describe the structure of hexagonal NaYF 4 , which is congruent with the result of PDF analysis . Besides, SSNMR spectroscopy has also been used to unravel the proximity of oleic acid ligands to the surface of UCNs, the dynamic crystallization process of UCNs in oxyfluoride glasses, , and the random occupation of Na + and Ln 3+ ions in cubic NaLnF 4 UCNs . Interestingly, for hexagonal NaScF 4 :Yb,Er UCNs, the doped Yb 3+ /Er 3+ ions preferred to substitute Na + rather than Sc 3+ ions because of the similar ionic radius …”
Section: Characterizations Of Local Structurementioning
confidence: 99%